Suwerenność państw w procesie integracji europejskiej - Malendowski, Włodzimierz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
The paper concerns an attempt to determine the status of European Union member states. It takes as its starting point the statement that the EU’s organizational structure provides for more than a confederation of states but less than a federation. At the present stage of the EU’s development a unique organization has been established that has not predecessor in the standards of international organizations. This is accompanied with a new approach to the interpretation of the nature of sovereignty of integrating European states, which is connected with intensifying processes of decomposition and the loosening of sovereign control by states over their territories and populations. States achieve their sovereign interests within the framework of international structures. They can also voluntarily restrict their sovereign rights on the basis of the commonly accepted rules and principles of international organizations. In this way they assign a comparative degree of state authorities’ competencies to these organizations. As a consequence, numerous issues that were formerly regulated by states are increasingly more often solved by means of corporate operations. This naturally leads to the states’ opening to the international environment without any threat to their sovereignty. The process of integration in Europe has not resulted in sovereignty of the European Union itself. Sovereignty remains an attribute of states. European states maintain their ability to